2009
DOI: 10.25011/cim.v32i1.5080
|View full text |Cite
|
Sign up to set email alerts
|

Terazosin treatment suppresses basic fibroblast growth factor expression in the rat ventral prostate

Abstract: Purpose: Alpha1-adrenergic receptor antagonists may not act solely on smooth muscle contractility. We evaluated the in vivo effect of the alpha1 blocker, terazosin, on the expression of basic fibroblast growth factor (bFGF) in the rat ventral prostate. Methods: Wistar rats were treated with terazosin (1.2 mg/ kg body weight, po, every second day) for 120 days. The expression of bFGF was assessed immuno-histochemically in tissue sections and by Western blotting in whole tissue preparations. Results: Terazosin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
5
0
3
Order By: Relevance
“…In rats, the in vivo administration of non-selective α 1 -adrenoceptor antagonists results in a reduction in prostatic weight 102 as well as cellular proliferation 103 . This effect appears to be dose dependent, as low doses of α 1 -adrenoceptor antagonist have no effect on prostatic weight 104 . Our observations with knockout mice (Fig.…”
Section: Age-related Changes In Prostate Innervationsupporting
confidence: 54%
“…In rats, the in vivo administration of non-selective α 1 -adrenoceptor antagonists results in a reduction in prostatic weight 102 as well as cellular proliferation 103 . This effect appears to be dose dependent, as low doses of α 1 -adrenoceptor antagonist have no effect on prostatic weight 104 . Our observations with knockout mice (Fig.…”
Section: Age-related Changes In Prostate Innervationsupporting
confidence: 54%
“…18 By contrast, the quinazoline-based ablockers (terazosin and doxazosin) were found to exert a potent apoptotic effect against prostate cancer cells through an a1-adrenoreceptor-independed pathway, caspace-3 and enhanced expression of transforming growth factor-b1. 18 By contrast, the quinazoline-based ablockers (terazosin and doxazosin) were found to exert a potent apoptotic effect against prostate cancer cells through an a1-adrenoreceptor-independed pathway, caspace-3 and enhanced expression of transforming growth factor-b1.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we have showed that terazosin may also exert its apoptotic action through a differential effect on the glycosaminoglycans and matrix metalloproteinase 2 of the rat prostate extracellular matrix (ECM) [13], and by inducing a considerable decrease in basic fibroblast growth factor (bFGF) immunohistochemical expression [14]. ECM regulates, among others, the trafficking of growth factors, while bFGF is one of the main promoters of cellular proliferation inducing epithelial growth [15].…”
Section: Introductionmentioning
confidence: 99%